(untitled) (Archives of Pediatrics of Uruguay, 2021)
Acute respiratory conditions are the first cause of consultation and hospital admission in the Winter months, being asthma the most important. Salbutamol is a bronchodilator with proven efficacy in exacerbations used first-line in treatment. The objective of this paper is to analyze two clinical cases of asthmatic children who presented adverse effects to salbutamol and required admission to the Intensive Care Unit. It is proposed to review the adverse effects of salbutamol used in asthmatic crises and to analyze therapeutic alternatives in this disease. Symptoms of side effects can be confused with those caused by the disease itself, determining the excessive use of this drug, thus, it is important to know the dosage profile and characterize the possible side effects to make rational and safe use of this drug.